Examining modification of the associations between air pollution and birth outcomes by neighborhood deprivation in a North Carolina birth cohort, 2011–2015 - Cowan, Kristen N.; Krajewski, Alison K.; Jimenez, Monica P.; Luben, Thomas J.; Messer, Lynne C.; Rappazzo, Kristen M. (Frontiers in Reproductive Health, 2024)
Background: Evidence from studies of air pollutants and birth outcomes suggests an association, but uncertainties around geographical variability and modifying factors remain. As neighborhood-level social characteristics are associated with birth outcomes, we assess whether neighborhood deprivation level is an effect measure modifier on the association between air pollution and birth outcomes in a cohort of births in North Carolina.Methods: Using birth certificate data, all North Carolina residential singleton live births from January 1, 2011 through December 31, 2015 with gestational ages 20-44 weeks (n=566,799) were examined for birth defect diagnoses and preterm birth. Exposures were daily-average fine particulate matter (PM2.5), daily 8-hour maximum nitrogen dioxide (NO2) and daily 8-hour maximum ozone (O3) modeled concentrations and the modifier of interest was the neighborhood deprivation index (NDI). Linear binomial models were used to estimate the prevalence differences (PD) and 95% confidence intervals (CI) for the association between ambient air pollution and birth defect diagnoses. Modified Poisson regression models were used to estimate risk differences (RD) and 95% CIs for air pollution and preterm birth. Models were stratified by neighborhood deprivation index group (low, medium or high) to assess potential modification by NDI.Results: Approximately 3.1% of the study population had at least one birth defect and 8.18% were born preterm. For preterm birth, associations with PM2.5 and O3 did not follow a conclusive pattern and there was no evidence of modification by NDI. The associations between NO2 and preterm birth were generally negative across exposure windows except for a positive association with NO2 and preterm birth for high NDI (RD: 34.70 (4.84, 64.56)) for entire pregnancy exposure. There was no evidence of associations between pollutants examined and birth defects.Conclusions: There may be differences in the association between NO2 exposure and preterm birth by NDI but we did not observe evidence of associations for birth defects. Our results support the public health protection afforded by reductions in air pollution, even in areas of neighborhood deprivation but future research conducted in areas with higher levels of air pollution and evaluating the potential for modification by neighborhood deprivation level would be informative.